Metabolic positron emission tomography/CT response after induction chemotherapy and chemo(re)irradiation is associated with higher negative resection margin rate in patients with locally recurrent rectal cancer. (16th November 2021) - van Zoggel, Desley M. G. I.; Voogt, Eva L. K.; van Lijnschoten, Ineke G.; Cnossen, Jeltsje S.; Creemers, Geert‐Jan; Nederend, Joost; Bloemen, Johanne G.; Nieuwenhuijzen, Grard A. P.; Burger, Pim J. W. A.; Lardenoije, Sabine G. G. F.; Rutten, Harm J. T.; Roef, Mark J.
Abstract: Aim: Positron emission tomography (PET)/CT can be used to monitor the metabolic changes that occur after intensified treatment with induction chemotherapy and chemo(re)irradiation for locally recurrent rectal cancer (LRRC). This study aimed to analyse the correlation between the PET/CT response and final histopathological outcomes. Methods: All LRRC patients who underwent induction chemotherapy prior to surgery between January 2010 and July 2020 and were monitored with pretreatment and post‐treatment PET/CT were included. Visual qualitative analysis was performed, and patients were scored as having achieved a complete metabolic response (CMR), partial metabolic response (PMR) or no response (NR). The histopathological response was assessed according to the Mandard tumour regression (TRG) score and categorized as major (TRG 1–2), partial (TRG 3) or poor (TRG 4–5). The PET/CT and TRG categories were compared, and possible confounders were analysed. Results: A total of 106 patients were eligible for analysis; 24 (23%) had a CMR, 54 (51%) had a PMR and 28 (26%) had NR. PET/CT response was a significant predictor of the negative resection margin rate, achieving 96% for CMR, 69% for PMR and 50% for NR. The overall accuracy between PET score and pathological TRG was 45%, and the positive predictive value for CMR was 63%. A longer interval between post‐treatment PET/CT and surgery negatively influenced the predictive value. Conclusion: Metabolic PET/CT response evaluation after neoadjuvant treatment proves to be a complementary diagnostic tool to standard MRI in assessing tumour response, and may play a role for treatment planning in LRRC patients.